Linking frugivore activity to early recruitment of a bird dispersed tree, Eugenia umbelliflora (Myrtaceae) in the Atlantic rainforest - Cortes, Marina Correa [UNESP]; Cazetta, Eliana [UNESP]; Staggemeier, Vanessa Graziele [UNESP]; Galetti, Mauro [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Seed dispersal by animals is a complex process involving several distinct stages: fruit removal by frugivores, seed delivery in different microhabitats, seed germination, seedling establishment, and adult recruitment. Nevertheless, studies conducted until now have provided scarce information concerning the sequence of stages in a plant's life cycle in its entirety. The main objective of this study was to evaluate the immediate consequences of frugivore activity for Eugenia umbelliflora ( Myrtaceae) early recruitment by measuring the relative importance of each fruit-eating bird species on the establishment of new seedlings in scrub and low restinga vegetation in the Atlantic rainforest, Brazil. We conducted focal tree observations on E. umbelliflora trees recording birds' feeding behaviour and post-feeding movements. We also recorded the fate of dispersed seeds in scrub and low restinga vegetation. We recorded 17 bird species interacting with fruits in 55 h of observation. Only 30% of the handled fruits were successfully removed. From 108 post flight movements of exit from the fruiting trees, 30.6% were to scrub and 69.4% to low restinga forest. Proportion of seed germination was higher in low restinga than in the scrub vegetation. Incorporating the probabilities of seeds' removal, deposition, and germination in both sites, we found that the relative importance of each frugivorous bird as seed dispersers varies largely among species. Turdus amaurochalinus and Turdus rufiventris were the best dispersers, together representing almost 12% probability of seed germination following removal. Our results show the importance of assessing the overall consequence of seed dispersal within the framework of disperser effectiveness, providing a more comprehensive and realistic evaluation of the relative importance of different seed dispersers on plant population dynamics.
Keywords: frugivory; gape width; seed dispersal effectiveness; seed germination; seed size